1966
DOI: 10.1029/wr002i003p00381
|View full text |Cite
|
Sign up to set email alerts
|

Use of unit‐source watersheds for hydrologic investigations in the semiarid Southwest

Abstract: The unit‐source watershed is an intermediate step between plots, in which certain runoff generative processes can be isolated, and large watersheds, the yields of which are controlled by the hydraulics of their complex channel systems. Several unit‐source watersheds have been instrumented within the Walnut Gulch experimental watershed in southeastern Arizona. Their comparative data indicate some basic hydrologic relationships between net runoff and size of drainage area, the significance of storm patterns, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 3 publications
(1 reference statement)
0
16
0
Order By: Relevance
“…They detected a 415% increase in the mesquite (i.e., shrub) and a 15% decrease in grass cover from 1973 to 1986. Kincaid et al [1966] noted that lower intensities of precipitation are required to produce runoff in the shrub‐covered subwatersheds of the WGEW than in the grass‐covered subwatersheds but in either cover type, runoff was far more dominated by rainfall characteristics. If mesquite behaves more like the common desert shrubs on the WGEW in terms of its partitioning of precipitation into runoff, this would imply an increase in runoff as vegetation changes from grass to mesquite.…”
Section: Resultsmentioning
confidence: 99%
“…They detected a 415% increase in the mesquite (i.e., shrub) and a 15% decrease in grass cover from 1973 to 1986. Kincaid et al [1966] noted that lower intensities of precipitation are required to produce runoff in the shrub‐covered subwatersheds of the WGEW than in the grass‐covered subwatersheds but in either cover type, runoff was far more dominated by rainfall characteristics. If mesquite behaves more like the common desert shrubs on the WGEW in terms of its partitioning of precipitation into runoff, this would imply an increase in runoff as vegetation changes from grass to mesquite.…”
Section: Resultsmentioning
confidence: 99%
“…Early research focused on describing hydrograph characteristics and the relationship between rainfall and runoff at a range of scales. For the small watersheds, Kincaid et al [1966] found that the decrease in runoff per unit area was valid from the plot to small watershed scale and that runoff was more dependent on rainfall characteristics than grass or shrub cover. Osborn and Lane [1969] quantified relationships between rainfall and runoff characteristics, finding that runoff rates and amounts were correlated with rainfall intensity and depth but that the amount of antecedent rainfall accounted for only 8% of the variation in observed runoff.…”
Section: Examples Of Data Usementioning
confidence: 99%
“…Without having an exact replica from one paired sub-watershed to the next, the direct comparison from one to another is full of potential error due to even the slightest differences in size, elevation, soil type, geology, vegetation, rainfall, topography, geomorphology and so on. However, the influence of land management on water supplies has been successfully documented using the paired-watershed approach and, hence, contributes to our understanding of the hydrologic cycle and the effects of management on it (Kincaid et al, 1966;Hornbeck, 1973;Bosch and Hewlett, 1982;Beschta et al, 2000;Ziemer and Ryan, 2000;Huang et al, 2003;Veum et al, 2009). Another limitation of the study is the lack of long-term monitoring (Wilm, 1949), especially in the case of wintertime rainfall, which is typically lower intensity, produces less runoff, and, due to its less erratic patterns, is presumably less sensitive to changes in infiltration (Kennedy et al, 2013).…”
Section: Limitations To Our Studymentioning
confidence: 99%